MICRO LIBRARY STANDS FOR COMMUNITY RESILIENCE USING LOCAL RESOURCES: AN SDGS OUTCOMES OF PUBLIC PARTICIPATION PRACTICE IN NGADIHARJO VILLAGE, MAGELANG, INDONESIA - Adelia, Nisa; Marihesya, Amelia (Merdeka Indonesia Jurnal International, 2023)
The diminishing revenue from agricultural sector in Ngadiharjo village (which has act as the leading sector) led the actor of one micro-library to seek for new opportunities. Harnessing the ample of bamboo as local potential and to test the ideas of making a worth-selling product, she promotes local society to produce besek – a multi-used box made from bamboo. The growth demands from regional and national market force the actor to set a knowledge-hub which has been transformed as a micro-library. With the assisted from Indonesian Ministry of Public Works and Housing; the micro-library develops a framework to contribute to the expand of society knowledge. This study aims to examine the works of micro-library and local resources in a small village in Indonesia towards the community resilience to deal with the economic needs. This study has been designed to answer these questions: How the actor of micro-library in Ngadiharjo village linked to the social learning process for society outcomes? What the contributions of local resources to achieve society outcomes? How the community resilience in Ngadiharjo village formed through the existence of micro-library as the knowledge hub? The social learning process as the SDGs based public participation framework’s outcomes and the existence of literacy ecosystem from the Literasi Untuk Kesejahteraan concept by Indonesian National Library will be use as the anchor to approach the micro-library role for community resilience in this area. The linkage of the micro-library actor, society capital and the implementation of knowledge sharing through micro-library programs; aim to present the finding of joining the society dots. A qualitative method with a descriptive approach applies for this study. Data collecting use observations, interviews and documentation process. Data analyse through data reduction and finding presentation. The study area is in Ngadiharjo village, Magelang, Indonesia, with a population of 4.939 Citizens To explore the data; a micro-library actor named Endah who managed TBM Omah Eling (a micro-library Omah Eling). This micro-library provides these programs for society: Money Literacy, Book For Free, Besek making training etc. By drawing the case in Ngadiharjo village, this study will present the importance of micro- library existence as knowledge-hub which potentially support local resources for being more productive and empowered. The local resources include the people (micro-library actor and local society) and the natural resources as the main materials to create products (by this case is bamboo to produce the multi-use box).